About One Cinema Ekphrasis of Sh. Abdullaev - A. A. Zhitenev (Научный диалог, 2021)
The results of the study of the genre form of ekphrasis in the context of the “visual turn” in the 1990—2000s are presented in the article. A particular case — Shamshad Abdullaev’s poem “Two Films”, which combines the impressions of two films by Spanish director Jose Luis Guerin “En la ciudad de Sylvia” (2007) and “Tren de sombras” (1997) are examined in the article. It has been established that this text is both a narrative about reception and an experience of “poetological” utterance, in which the poet speaks about his understanding of the essence of art, the nature of the creative act, connections between poetry and visual imagery. This is a “complex ekphrasis”, involving the alignment of motives and plots of different works in a single semantic series. Ekphrastic description includes both the reproduction of plot-significant scenes and the peculiarities of the film language. It is proved that the reception of cinema is mediated by other artistic codes (photography, literature), complicated by reflection on the language of philosophy and aesthetics (“mono no aware”, “nunc stans”). The semiotics of the visual, therefore, arises at the intersection of different cultural codes and contexts.